Film routes in Basilicata - Delio Colangelo (Netcom)
A classical definition of landscape is “nature perceived through a culture”. On the “historicity” of the landscape, some authors have underlined the cinema’s capacity to register the transformations of the territory and, at the same time, to direct the gaze on it. Since the end of the Second World War, the Basilicata region has been a film location; more than forty full length movies have been shot in Basilicata. Most of them, from The Gospel According to St. Matthew by Pier Paolo Pasolini to Christ stopped at Eboli by Francesco Rosi, have shown the misery and the backwardness of Basilicata, inspired by the works of some authors as Carlo Levi and Ernesto De Martino. In the last years, Basilicata has been the location of some worldwide box office hits: The Passion, Ben Hur, Wonder Woman. The paper presents a project of film routes, developed by Basilicata Region, Eni Enrico Mattei Foundation, Gal Bradanica, and Osservatorio del Cineturismo aiming at make available the cinematic landscapes.